"Man måste jobba över alla gränser" - En studie om MultifunC ur ungdomsbehandlande personals perspektiv. - Nouparvar,Nima (2024)
The purpose of this study was to investigate the staff’s perspective when working with young criminals using the methods of MultifunC as a treatment process. The method used was qualitative and the empirical material was collected through semi-structured interviews with four persons holding different positions within the organisation. For the analysis the theoretical approaches of Systems Theory and Goffman’s masks were applied. The results show that the interviewees strongly trust the MultifunC as a treatment method because they understand it as based on reliable evidence-based research. It is also clear that they see the method as demanding and needing the right amount and kind of resources to be efficient for the youth. The analysis shows that the youth under treatment are never seen as disconnected individuals but as part of larger systems, where the family forms an important part. MultifunC’s aim to not let go of the youth too early and to also work with their families is seen as a way to allow the youth to change their ‘masks’ and bring with them a renewed social role after the treatment.